“BIOANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR ESTIMATION OF PROPOFOL IN K3EDTA HUMAN PLASMA BY USING LC-ESI-MS/MS” - Kumar, Ashok; Joshi, Dr. D.B.; Bhadauria, Dr. R.S. (Journal of Biomedical and Pharmaceutical Research, 2019)
Bioanalytical method development is the process of creating a procedure to enable a compound of interest to be identified and quantified in a biological matrix. A compound can often be measured by several methods and the choice of analytical method involves many considerations. Analysis of drugs and their metabolites in a biological matrix is carried out using different extraction techniques like liquid-liquid extraction, solid phase extraction (SPE) and protein precipitation from these extraction methods samples are spiked with calibration (reference) standards and using quality control (QC) samples. These methods and choice of analytical method describes the process of method development and includes sampling, sample preparation, separation, detection and evaluation of the results. The developed process is then validated. These Bioanalytical validations play a significant role in evaluation and interpretation of bioavailability, bioequivalence, pharmacokinetic, and toxicokinetic studies. In which different parameters like accuracy, precision, selectivity, sensitivity, reproducibility, and stability are performed. Keywords: - LLE, SPE, Quality control samples, Bioequivalence, Bioavailability, Validation.